A Case of Leukocytoclastic Vasculitis and Associated Conjunctivitis Following MMR Vaccine Administration - Hana I. Nazir; Aubrey A. Hess; Abha Soni; Kathryn A. Potter (Case Reports in Dermatological Medicine)
Introduction. Leukocytoclastic vasculitis (LCV) is a small-vessel vasculitis characterized by immune complex deposition in the walls of dermal capillaries and venules. With the COVID-19 pandemic, more adults are receiving the MMR vaccine, as it may enhance innate immune responses against COVID-19 infection. Here, we report a case of LCV and associated conjunctivitis arising in a patient secondary to immunization with the MMR vaccine. Methods and Results. A 78-year-old man on lenalidomide therapy for multiple myeloma presented to an outpatient dermatology clinic with a two-day history of a painful rash consisting of scattered pink dermal papules on bilateral dorsal and palmar hands, as well as bilateral conjunctival erythema. Histopathological findings—which revealed an inflammatory infiltrate with papillary dermal edema, as well as nuclear dust within small blood vessel walls with extravasation of red blood cells—were most consistent with LCV. It then became known that the patient had received an MMR vaccine two weeks prior to the onset of the rash. The rash was resolved with the use of topical clobetasol ointment, and the patient’s eyes were cleared as well. Conclusions. This is an interesting presentation of MMR vaccine-related LCV occurring only on the upper extremities with associated conjunctivitis. Had the patient’s oncologist not known about the recent vaccination, it is likely that the treatment of his multiple myeloma would have been postponed or altered, as lenalidomide can also cause LCV.